2015
DOI: 10.1080/08927022.2015.1010083
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for the simulation of steady-state diffusion through membranes: pressure-tuned, boundary-driven molecular dynamics

Abstract: We present a novel molecular dynamics-based simulation technique for investigating gas transport through membranes. In our simulations, the main control parameters are the partial pressure for the components on the input side of the membrane and the total pressure on the output side. The essential point of our scheme is that this pressure control should be realised by adjusting the particle numbers in the input and output side control cells indirectly. Although this perturbation is applied sufficiently far fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Here we note that in MD simulations of membranes creating a vacuum effect is a challenging task as also mentioned by others. 15 , 21 To create the vacuum effect, a larger outlet force constant, k O i , was used compared to the inlet force constant, k I i . The values of parameters used in eqn (1) & (2) and the locations of the force and control regions are given in Table S2.…”
Section: Models and Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we note that in MD simulations of membranes creating a vacuum effect is a challenging task as also mentioned by others. 15 , 21 To create the vacuum effect, a larger outlet force constant, k O i , was used compared to the inlet force constant, k I i . The values of parameters used in eqn (1) & (2) and the locations of the force and control regions are given in Table S2.…”
Section: Models and Computational Detailsmentioning
confidence: 99%
“… 14 However, DCV-GCMD method doesn't work efficiently for dense fluids due to the extremely low acceptance rates for the insertion and deletion of the molecules. Moreover, according to Ható et al 15 coupling MC moves with MD can be problematic since the ratio of insertion/deletion steps vs. MD steps should be optimized in order to perform a reliable simulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that while all properties calculated and monitored in the control cells predominantly stem from the movements and interactions of particles in these regions, the artificial perturbation of the system is only present in the boundary regions of the simulation cell [18]. Our earlier test clearly showed that the particles inserted into the system have no "memories" of their initial velocities before they reach the interaction range of the membrane [19].…”
Section: Transport Simulation Methodsmentioning
confidence: 89%